Indian Sign Language Research and Training Centre - Shree, Sonam (THE PRIMARY TEACHER, 2019)
Language is the medium through which thoughts, emotions, and experiences are shared, forming the foundation of human connection. While spoken languages are the most widely used means of communication, they are not the only ones. Sign languages offer a unique and profound way for the deaf and hard-of-hearing community to communicate, connect and express themselves. One such is the Indian Sign Language (ISL). The common perception is that deaf people communicate through gestures, which are limited in nature. However, sign languages possess intricate grammar and rich cultural significance. The ISL plays a pivotal role in shaping the lives of millions in India, bridging communication barriers and enriching cultural diversity